Double external defibrillation in the emergency department: A rapid review of the literature / La double défibrillation externe à l’urgence : une revue rapide de la littérature - Tessier, William; Blais, Sabrina; Provost, Josiane; Ouellet, Simon (Canadian Journal of Emergency Nursing / Journal canadien des infirmières d’urgence, 2025)
Context: In the context of refractory cardiac arrest, dual external defibrillation (DED) has been attracting growing interest in recent years. Unlike traditional defibrillation, DED uses two defibrillators, either simultaneously or sequentially, to deliver shocks. This approach aims to maximize the likelihood of restoring a normal heart rhythm when conventional techniques fail. Although several studies have looked at DED in prehospital settings, there is a notable lack of data on its use in a hospital setting, particularly in the emergency department.Objective: To synthesize current knowledge on the use of DED in hospital settings, focusing on reported practices and issues related to its implementation.Methodology: A rapid review of the literature was conducted in accordance with the methodological recommendations of the Cochrane Rapid Review Methods Group (Garritty et al., 2024). The PubMed, MEDLINE, EMBASE, CINAHL et Cochrane Library databases were consulted.Results: The initial search identified 356 articles published between 2004 and 2024. A total of 15 articles were selected, detailing 18 case reports. Analysis of the cases highlighted the potential benefits, limitations, and risks associated with the use of DED in hospital settings.Conclusion: DED is a technique generally used as a last resort, after traditional methods have failed. To date, the limited robustness of the available studies does not allow its effectiveness to be established in comparison with simple defibrillation. Randomized controlled trials are therefore necessary to confirm its effectiveness. For future practice, the uniqueness of clinical cases must be considered and a risk-benefit analysis must be undertaken by healthcare teams during prolonged resuscitation. Standardization of procedures will also be essential to ensure optimal use of DED.